Effect of wind barrier setting angle on the occurrence patterns of low oxygen gas in upper corner - YUAN Junwei; NIE Jinlong; LI Long; DU Yongkun; GUO Yanmei; WU Ran (矿业科学学报)
Changes of wind barrier angles exert significant effect on the occurrence of low oxygen gas in the upper corner. Taking the 100510 working face of a mine in Shanxi Province as example, this study uses Ansys Fluent software to build a gas migration model of the working face to simulate the occurrence patterns of low oxygen gas in the upper corner under different wind barrier angles, and verifies the model through field measurement. Results show that setting wind barrier could increase wind speed in the upper corner, which offers a solution to the low oxygen problem in upper corner. The optimal treatment of low oxygen in the upper corner is realized with wind barrier angle set at 60° at the position 5m away from the return air channeling. This study provides implications for solutions to the low oxygen issue in the upper corner and thereby ensure safety production.